Sistem Informasi Pertumbuhan Data Penduduk Pada Dinas Penduduk Dan Catatan Sipil Pemerintah Kota Banjarmasin Berbasis Website - Rosyadi, Muhammad; Rusyadi, Muhammad (mijournal.org, 2024)
PT. Geoinfo Teknologi collaborates with the Population and Civil Registration Office of Banjarmasin City to enhance the efficiency of population growth data management, which has been conducted manually. This study aims to design and develop a web-based information system that enables sub-districts to directly input family card data, allowing population growth charts to be automatically updated. The study focuses on managing family card data, living and deceased population data, birth records, and growth reports based on specific categories. This system is expected to streamline data management processes, provide accurate information, and support decision-making at the Population and Civil Registration Office of Banjarmasin City.